2018
DOI: 10.1186/s12936-018-2433-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of primaquine in normal human volunteers: investigation of phase I and phase II metabolites from plasma and urine using ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry

Abstract: BackgroundPrimaquine (PQ), an 8-aminoquinoline, is the only drug approved by the United States Food and Drug Administration for radical cure and prevention of relapse in Plasmodium vivax infections. Knowledge of the metabolism of PQ is critical for understanding the therapeutic efficacy and hemolytic toxicity of this drug. Recent in vitro studies with primary human hepatocytes have been useful for developing the ultra high-performance liquid chromatography coupled with high-resolution mass spectrometric (UHPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…Carboxyprimaquine, which is produced through the monoamine oxidase pathway [13] and not thought to have antimalarial activity, had a lower C max and AUC ∞ in the NM group, perhaps reflecting its increased metabolism through the CYP2D6 pathway. Levels of the 2-, 3- and 4-hydroxyprimaquine metabolites and 5,6-ortho-quinone were not appreciable in plasma specimens, unlike past murine studies at WRAIR [10], although levels were similar to those from a recent PK study in 7 healthy volunteers in the United States [12]. The inherent instability of the compounds, loss during processing and freezing, or location in other compartments (eg, erythrocytes and tissues) represent possible explanations.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Carboxyprimaquine, which is produced through the monoamine oxidase pathway [13] and not thought to have antimalarial activity, had a lower C max and AUC ∞ in the NM group, perhaps reflecting its increased metabolism through the CYP2D6 pathway. Levels of the 2-, 3- and 4-hydroxyprimaquine metabolites and 5,6-ortho-quinone were not appreciable in plasma specimens, unlike past murine studies at WRAIR [10], although levels were similar to those from a recent PK study in 7 healthy volunteers in the United States [12]. The inherent instability of the compounds, loss during processing and freezing, or location in other compartments (eg, erythrocytes and tissues) represent possible explanations.…”
Section: Discussionmentioning
confidence: 58%
“…By using recombinant CYP2D6, in vitro experiments have been able to detect phenolic metabolites of PQ [8], and in vivo studies in mice have confirmed CYP2D metabolism in the PQ pathway by measuring metabolites such as 2-, 3-, and 4-hydroxyprimaquine and 5,6-ortho-quinone in the blood [9–11]. Recently, a human PQ pharmacokinetic (PK) study detected 5,6-ortho-quinone in the urine, although the CYP2D6 genotype of these 7 healthy adult volunteers was not determined [12]. Although the 5,6-ortho-quinone is not active itself, it is a stable surrogate marker for the presence of 5-hydroxyprimaquine, the unstable PQ metabolite generated through 2D6, which is believed to be necessary for radical cure through the generation of oxidative stress from redox cycling [13].…”
mentioning
confidence: 99%
“…More positively, such variability offers hitherto unavailable opportunities for demonstrating hepatocyte factor(s) acting as defining determinants of anti-parasitic activity of PQ. That understanding, in turn, may directly inform strategies for elucidating the molecular basis of its potentiation by CQ.Detailed analysis in human volunteers revealed complex pathways that generate numerous PQ metabolites(14), with the production of some but not others by ex vivo culturedon November 1, 2020 by guest http://aac.asm.org/ Downloaded from 6 hepatocytes influenced by the concurrent presence of CQ (15). The decrease of the CYP2D6dependent PQ metabolites by CQ may favour the production of other active metabolites.…”
mentioning
confidence: 99%
“…Mean maximal daily plasma concentrations with 60-mg doses varied between 54 and 2,924 g/liter on the third day and 89 and 1,400 g/liter on the sixth day, with the lower and higher values representing the values for the same subjects on each day. This interindividual variability in plasma levels appeared with all of the experimental 8-aminoquinolines evaluated (17) and may reflect the then unknown importance of inherent variability in the catalytic activity of the cytochrome P-450 2D6 isozyme in the metabolism of 8-aminoquinolines (79)(80)(81). In 1981, Carson et al (17) pointed out the seemingly paradoxical inverse relationship between the plasma levels of the parent drug and therapeutic activity, perhaps explained by the extent of conversion of the parent drug to the active metabolite(s).…”
Section: Blood Schizontocide Impacts On 8-aminoquinoline Toxicitymentioning
confidence: 96%
“…Among the many metabolic derivatives known, the 5-hydroxylated species (with perhaps variable modifications to the 8-amino alkyl chain) emerge as probably the most relevant (76,77). These highly redox-reactive derivatives appear to be generated by the 2D6 isozyme of cytochrome P-450 (CYP2D6), and their relatively minute amounts and instability impose technical challenges in studying them (78)(79)(80). The most widely studied metabolite, a carboxylated species of the parent drug (carboxyprimaquine) produced by reaction with monoamine oxidase, also happens to be the most abundant, stable, slowly eliminated, and easily detected, but it is without apparent therapeutic or toxic activity (81,82).…”
Section: Metabolismmentioning
confidence: 99%